Voice Disorder: case definition and prevalence in teachers Disfonia: definição de caso e prevalência em professores - Renata Jardim; Sandhi Maria Barreto; Ada Ávila Assunção (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2007)
Several studies have shown a high prevalence of voice disorders among teachers. However, it is difficult to establish comparisons among the results found given the great variability among criteria and symptoms used to define the presence of vocal alteration, in addition to the variations in the composition of the populations studied (age, gender, origin, working schedule, profession, among others). This study aims to discuss the need for a standard definition of functional voice disorder and possible implications of the lack of such a standard definition on estimating the prevalence of functional voice disorders among teachers. A systematic bibliographic review on voice disorders in teachers was carried out as of 1990 in the Medline, Scielo, Ovid, Pubmed and Lilacs databases. Of the 3,186 citations, 15 fulfilled the inclusion criteria to discuss prevalence of vocal disorder in teachers. Nine articles defined vocal disorder based solely on the presence of vocal symptoms, which varied in relation to type, number, frequency, and reference period. Hoarseness and vocal tiredness were mentioned in all studies that evaluated vocal symptoms. Only three studies reported prevalence based on professional examination. Prevalence rates varied according to reference period and frequency of symptoms. The results ratified the importance of standardizing the case definition of voice disorder in order to better study and understand its occurrence and to compare prevalence obtained from different populations and along time in the same population. Standardized definitions should include laryngeal alterations observed in later phases of voice disorder as well as signs and symptoms present in phases previous to organic alterations, when they are potentially reversible. Várias pesquisas têm mostrado elevada prevalência de disfonia em professores, porém não há uma definição padronizada de alteração vocal nos estudos realizados, o que dificulta a comparação dos resultados obtidos e o desenvolvimento da pesquisa na área. O objetivo deste estudo foi discutir a necessidade de padronizar a definição de disfonia funcional e discutir possíveis implicações da falta da padronização na estimação da prevalência da disfonia funcional em professores. Foi realizada uma revisão bibliográfica sistemática sobre disfonia em professores, por meio de consulta a diversas bases de dados, sendo considerados os artigos publicados a partir de 1990. De 3.186 citações, 15 artigos preencheram os critérios de inclusão para a discussão da prevalência da disfonia em professores. Nove artigos definiram disfonia baseados somente na presença de sintomas vocais, com variações em relação ao tipo, número, freqüência e período de referência. Rouquidão e cansaço vocal foram mencionados em todos os estudos que avaliaram sintomas vocais. Somente três estudos analisaram a prevalência da disfonia baseada na avaliação profissional. As prevalências variaram conforme o período de referência e a freqüência dos sintomas pesquisados. Os resultados ratificaram a importância de padronizar a definição de disfonia para melhor estudar e compreender a sua ocorrência e comparar a prevalência obtida em diferentes populações e através do tempo, em uma mesma população. A definição padronizada da disfonia deveria incluir alterações laríngeas observadas em fases mais avançadas da disfonia, assim como sinais e sintomas presentes em fases que precedem as alterações orgânicas, potencialmente reversíveis.